APPLICATION ARABIC LEARNING BASED ON MULTIMEDIA USING ASYNCHRONOUS METHOD - Wawan Gunawan (Bakti Nusantara Institute, 2020)
Every school has different featured programs but it has similar goals to educate the nation based on faith and piety on Quran and As-Sunnah. Daily conversation will often be used between the school and the student's parents, both basic and later. To obtain maximum results in the learning process, it is necessary to use Arabic communication between the parents and the students outside the school. There are Parents difficulties to speak Arabic daily conversation to support the teaching and learning process at school and home. There is a deadlock between parents and students due to parents' lack of understanding in Arabic. How to helping the realization of the Arabic learning process given to students outside the school environment by repeating the learning process with parents with multimedia application tools and building Arabic learning applications by using asynchronous based multimedia applications.